A multi-source remote sensing dataset for large-scale forest monitoring - D’Amico, Giovanni; Botticelli, Davide; Marcelli, Giacomo; Mattioli, Walter; Chirici, Gherardo; Vangi, Elia; Borghi, Costanza; Corona, Piermaria; Schumacher, Johannes; Breidenbach, Johannes; Su, Yang; Mehtätalo, Lauri; et al. (Elsevier, 2026)
This data article presents a multi-source dataset of satellite-based auxiliary data designed for forest modelling and monitoring. The dataset integrates annual medoid composites derived from Sentinel-1, Sentinel-2, and Landsat imagery, together with spectral indices, Landsat-based 3I3D change metrics, forest mask and forest type layers, and terrain variables derived from the Copernicus GLO-30 DEM, offering comprehensive information on forest cover, spectral behavior, and change metrics. It provides harmonized predictors across seven European countries, ensuring consistency, scalability, and ease of use for researchers developing or validating models to understand forest dynamics and estimate forest-related variables such as biomass or canopy recovery. A curated subset of the dataset is distributed via Zenodo, along with direct public access links to the complete multi-terabyte archive. The data support applications in forest biodiversity conservation, carbon monitoring, biomass modelling, and climate-change impact assessment.
Keywords: Copernicus; forest multifunctionality; Google earth engine; landsat